Facile morphology control of gold(0) structures from aurophilic assemblies. Issue 14 (17th March 2020) - Aguiló, Elisabet; Dalmases, Mariona; Lin, Mengxi; Lima, João Carlos; Gavara, Raquel; Figuerola, Albert; Llorca, Jordi; Rodríguez, Laura
Abstract : Different gold microstructures have been synthesized by using supramolecular gold(i ) organometallic compounds as templates and Ag nanoparticles as reducing agents. Abstract : Different gold microstructures have been synthesized by using supramolecular gold(i ) organometallic compounds as templates and Ag nanoparticles as reducing agents. The use of fibers resulting from supramolecular assemblies of neutral gold(i ) compounds gives rise to the formation of microrods. The use of supramolecular assemblies from ionic molecules results in spherical or square-based prism gold microstructures, depending on the shape of the supramolecular gold(i ) precursor assembly. In addition to temperature and reaction time, solvents exert a strong influence on the formation and morphology of gold structures, as borne out by the example that well-defined star-like morphologies have been obtained in chloroform.